Learning styles: A review / Badli Esham Ahmad - Ahmad, Badli Esham (2006)
Learning style is the way in which each learner begins to concentrate on, process, and retain new and difficult information. There are various learning styles which measure different ways learners acquire second language perceptual, character and cognitive. Various instruments are used to measure learning styles; questionnaire and test. However, opponents of learning styles have argued over the lack of strong theoretical underpinnings on the subject, various definitions given on the subject and the language obstacles in the instruments themselves. This paper looks into the various ways that learners learn language based on their differences in learning styles, thus, allowing for better pedagogical instructions toward language classroom.